Pengaruh Dana Alokasi Umum (DAU) dan Dana Alokasi Khusus (DAK) terhadap Tingkat Kemiskinan di Provinsi Aceh - Della Kurniawati; Puti Andiny; Yani Rizal; Safuridar Safuridar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Poverty is a major problem that occurs in every country and region including Aceh Province. According to the Central Bureau of Statistics (BPS) report in 2023, Aceh Province ranked first with the highest poverty rate when compared to other regions on the island of Sumatra, Indonesia. This study aims to determine the effect of the General Allocation Fund (DAU) and the Special Allocation Fund (DAK) on the poverty rate in Aceh Province. The data used is secondary data and is quantitative data. The data uses time series data from 2011-2023, namely for 13 years obtained from BPS. The results showed that DAU has a t-statistic value of 3.198397 with a probability significance value of 0.0095 which is <0.05, it can be concluded that DAU has a significant effect on the poverty rate. DAK has a t-statistic value of -2.428359 with a probability significance value of 0.0355 where <0.05, it can be concluded that DAK has a negative effect on the poverty rate.